2005
DOI: 10.1530/rep.1.00430
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of apoptosis in the atresia of dominant bovine follicles of the first follicular wave following ovulation

Abstract: During atresia of bovine follicles, granulosa cells are lost through the controlled form of cell death, apoptosis. The purpose of this study was to characterize the regulation of apoptotic death of granulosa cells in dominant bovine follicles during the first wave of follicular development. Dominant follicles were collected from Holstein heifers on days 4, 6 or 8 of the first follicular wave (n 5 5/day). Regulation of apoptosis in granulosa cells was examined by annexin V and propidium iodide staining; measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 52 publications
3
34
0
4
Order By: Relevance
“…Once cyclic recruitment commences groups of antral follicles grow as in a 'wave'. The first wave of an oestrous cycle is initiated 1-2 days after ovulation (Valdez et al 2005) and the number of follicular waves per cycle (2 or 3) is determined by the duration of the luteal phase (Fortune 1994). Large variation exists between animals in terms of number of follicles per wave (range 11-54), principally due to differences in the numbers of small follicles (those w3 mm in diameter).…”
Section: Introductionmentioning
confidence: 99%
“…Once cyclic recruitment commences groups of antral follicles grow as in a 'wave'. The first wave of an oestrous cycle is initiated 1-2 days after ovulation (Valdez et al 2005) and the number of follicular waves per cycle (2 or 3) is determined by the duration of the luteal phase (Fortune 1994). Large variation exists between animals in terms of number of follicles per wave (range 11-54), principally due to differences in the numbers of small follicles (those w3 mm in diameter).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, markers of follicular dominance such as estradiol concentration in the follicular fluid and transcript levels of LHCGR and CYP19A1 in granulosa cells are used to confirm the follicular status (Evans and Fortune, 1997;Evans et al, 2004;Mihm et al, 2006;Gasperin et al, 2014). It has been reported that by day 6 (considering day 1 as the day when two or more follicles greater than 4 mm in diameter were observed), under high progesterone levels, the dominant follicle shows early signs of atresia such as decreased estradiol concentrations, and increased percentage of apoptotic cells (Valdez et al, 2005).…”
Section: Follicular Deviationmentioning
confidence: 99%
“…Each primordial follicle consists of a primary oocyte arrested in prophase of meiosis I in the diplotene stage, which is surrounded by a single layer of pregranulose cells (18) . During the course of the reproductive life of the female, a cohort of primordial follicles are recruited continuously and cyclically from the set of primordial follicles in resting to grow and differentiate themselves (15) , of these, more than 99.9 % are not used due to atresia (15,19) . The start of the folliculogenesis is characterized by the transition of flat pregranulosa cells to cuboidal granulosa, giving rise to the primary follicle.…”
Section: Efecto De Los Genes Maternos Sobre La Maduración Del Ovocitomentioning
confidence: 99%
“…These cells are separated from the granulosa cells by a basement Cuadro 2. Genes con efecto materno identificados en el bovino reclutados continua y cíclicamente a partir del conjunto de folículos primordiales en reposo para crecer y diferenciarse (15) , de estos, más del 99.9 % no son utilizados debido a la atresia (15,19) . El inicio de la foliculogénesis se caracteriza por la transición de células pregranulosa planas a cuboidales de la granulosa, que dan lugar al folículo primario.…”
Section: Efecto De Los Genes Maternos Sobre La Maduración Del Ovocitounclassified